Controlled ligand distortion and its consequences for structure, symmetry, conformation and spin-state preferences of iron(ii) complexes12. Issue 44 (21st October 2015) - Kroll, Nicole; Theilacker, Kolja; Schoknecht, Marc; Baabe, Dirk; Wiedemann, Dennis; Kaupp, Martin; Grohmann, Andreas; Hörner, Gerald
Abstract : Angular constraints in the backbone of pentadentate ligands are employed to tune the electronic and geometric structure of iron(ii ) complexes via incremental distortion of the ligand field. Abstract : The ligand-field strength in metal complexes of polydentate ligands depends critically on how the ligand backbone places the donor atoms in three-dimensional space. Distortions from regular coordination geometries are often observed. In this work, we study the isolated effect of ligand-sphere distortion by means of two structurally related pentadentate ligands of identical donor set, in the solid state (X-ray diffraction, 57 Fe-Mössbauer spectroscopy), in solution (NMR spectroscopy, UV/Vis spectroscopy, conductometry), and with quantum-chemical methods. Crystal structures of hexacoordinate iron(ii ) and nickel(ii ) complexes derived from the cyclic ligand L 1 (6-methyl-6-(pyridin-2-yl)-1, 4-bis(pyridin-2-ylmethyl)-1, 4-diazepane) and its open-chain congener L 2 ( N 1, N 3, 2-trimethyl-2-(pyridine-2-yl)- N 1, N 3 -bis(pyridine-2-ylmethyl) propane-1, 3-diamine) reveal distinctly different donor set distortions reflecting the differences in ligand topology. Distortion from regular octahedral geometry is minor for complexes of ligand L 2, but becomes significant in the complexes of the cyclic ligand L 1, where trans elongation of Fe−N bonds cannot be compensated by the rigid ligand backbone. This provokes trigonal twisting of the ligand field. This distortion causes the metal ion in complexes of L 1 to experience a significantly weaker ligand field than in the complexes of L 2, which are more regular. The reduced ligand-field strength in complexes of L 1 translates into a marked preference for the electronic high-spin state, the emergence of conformational isomers, and massively enhanced lability with respect to ligand exchange and oxidation of the central ion. Accordingly, oxoiron(iv ) species derived from L 1 and L 2 differ in their spectroscopic properties and their chemical reactivity.